Contacting with Violent Patterns and Violent Peer and Student’s Violent Drift: An Application of Edwin Sutherland’s Differential Association Theory - Nhu Trang, Nguyen Thi (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Applying Edwin Sutherland’s Differential Association theory, this article attempts to explain the conditions facilitating student violence in Hanoi’s high-schools. Data for this article was collected through participant observation at a high-risk school in Hanoi, in-depth interviews with different stakeholders, and self-administered questionnaire survey at three high-schools. Results support differential association propositions that contact with violent patterns and having aggressive peers increase students’ drift toward violent solutions. Some illustration of the mechanism in which contact with violent pattern and peers encourage students to resort to violence, and further discussion on the application of differential association theory in the context of Vietnam are also presented. Received 21st September 2017; Revised 12nd October 2017; Accepted 30th October 2017